Repurposing approved drugs as potential inhibitors of 3CL-protease of SARS-CoV-2: Virtual screening and structure based drug design. (October 2020) - Meyer-Almes, Franz-Josef
Graphical abstract: Highlights: Virtual screening of FDA drugs yields potential therapeutics against COVID19. Hit compounds are supposed to inhibit SARS-CoV-2 main protease 3CL pro . Best hits include oxytetracycline and other antibiotics. Abstract: 3CL proteases (3CL pro ) are only found in RNA viruses and have a central role in polyprotein processing during replication. Therefore, 3CL pro has emerged as promising drug target for therapeutic treatment of infections caused by Coronaviruses. In the light of the recent major outbreak of the SARS-CoV-2 virus and the continuously rising numbers of infections and casualties, there is an urgent need for quickly available drugs or vaccines to stop the current COVID-19 pandemic. Repurposing of approved drugs as 3CL pro inhibitors could dramatically shorten the period up to approval as therapeutic against SARS-CoV-2, since pharmacokinetics and toxicity is already known. Several known drugs, e.g. oxytetracycline, doxorubicin, kanamycin, cefpiramide, teniposide, proanthocyanidin and salvianolic acid B, but also not-approved active compounds from the ZINC15 library were identified as new potential inhibitors of 3CL pro by using different complementary virtual screening and docking approaches. These compounds have the potential to be further optimized using structure based drug design as demonstrated for oxytetracycline.